Pediatric Health Care Provider Perceptions of Weight Loss Surgery in Adolescents. (January 2014) - Vanguri, Poornima; Lanning, David; Wickham, Edmond P.; Anbazhagan, Aruna; Bean, Melanie K.
This study explored pediatric health care providers' obesity treatment practices and perceptions about adolescent weight loss surgery (WLS). Surveys were e-mailed to pediatric listservs. After descriptive analyses, correlations, chi-squares, and one-way analyses of variance compared responses by provider characteristics. Surveys were completed by 109 providers. Almost half do not routinely measure body mass index. Providers typically counsel patients about lifestyle change, with limited perceived benefit; <10% have ever referred patients for WLS, citing cost (20%), risk (49%), or "not indicated in pediatrics" (17%) as reasons. However, when presented with patient scenarios of different ages and comorbidities, likeliness to refer for WLS increased substantially. Surgeons, younger providers and those with fewer years of experience were more likely to refer for WLS ( P < .05). Despite expert consensus recommendations supporting WLS as part of a comprehensive obesity treatment plan, significant pediatric provider resistance to refer obese adolescents remains. Improved referral and management practices are needed.